Gold nanoparticle biodissolution by a freshwater macrophyte and its associated microbiome. Issue 11 (November 2018) - Avellan, Astrid; Simonin, Marie; McGivney, Eric; Bossa, Nathan; Spielman-Sun, Eleanor; Rocca, Jennifer; Bernhardt, Emily; Geitner, Nicholas; Unrine, Jason; Wiesner, Mark; Lowry, Gregory
Abstract Predicting nanoparticle fate in aquatic environments requires mimicking of ecosystem complexity to observe the geochemical processes affecting their behaviour. Here, 12 nm Au nanoparticles were added weekly to large-scale freshwater wetland mesocosms. After six months, ~70% of Au was associated with the macrophyteEgeria densa, where, despite the thermodynamic stability of Au0 in water, the pristine Au0 nanoparticles were fully oxidized and complexed to cyanide, hydroxyls or thiol ligands. Extracted biofilms growing onE. densa leaves were shown to dissolve Au nanoparticles within days. The Au biodissolution rate was highest for the biofilm with the lowest prevalence of metal-resistant taxa but the highest ability to release cyanide, known to promote Au0 oxidation and complexation. Macrophytes and the associated microbiome thus form a biologically active system that can be a major sink for nanoparticle accumulation and transformations. Nanoparticle biotransformation in these compartments should not be ignored, even for nanoparticles commonly considered to be stable in the environment. Gold nanoparticles typically considered inert in oxic waters accumulate in freshwater wetland subaquatic plants and are completely biotransformed to oxidized Au species by the associated cyanogenic biofilm.